The Dynamics of Social Inequality in the Kali Gandaki ‘A’ Dam Project in Nepal: The Politics of Patronage - Rai, Kavita (Hydro Nepal: Journal of Water, Energy and Environment, 2008)
This research article utilizes concepts from the ‘Anthropology of Clientelism’ to explain the dynamics of social inequality after the construction of the Kali Gandaki ‘A’ hydroelectric dam project. As Nepal’s rural societies are largely agrarian, Scott’s (1976) moral economy theory, positioned against Popkin’s (1979) political economy approach acts as the basis of argumentation of how patronage politics links the different social strata at the local level. The access to the KG ‘A’ project resources (financial in terms of compensation and project employment and natural in regard to access to land and water) and the acquired outcomes explains the strategies that local actors took to gain from the project intervention eventually changing the dynamics of social interaction and levels of inequalities internal and external to their own social groups.Key words: Dam, clientelism, compensation, Kali Gandaki ‘A’, patronage, resettlement, social inequalities, NepalHydro Nepal: Journal of Water, Energy and Environment Vol. I, Issue No. 1 (2007) pp. 22-28